Magnetic ordering and dynamics in the XY pyrochlore antiferromagnet: a muon-spin relaxation study of Er2Ti2O7 and Er2Sn2O7 - Lago, J; Lancaster, T; Blundell, S; Bramwell, S; Pratt, F; Shirai, M; Baines, C (2005)
Spin dynamics in Er2 and 2Sn2O7 have been probed by means of muonspin relaxation (μ+SR) in the temperature range 0.02 ≤ T ≤ 300 K. Both compounds are thought to constitute experimental realizations of the highly frustrated XY antiferromagnet on the pyrochlore lattice, for which theory predicts fluctuation-induced magnetic order. Our results for Er2Ti2O7 are consistent with a transition into an ordered state at TN ∼ 1.1 K, in agreement with previous neutron measurements. Below this temperature, the muon relaxation rate λ(T) remains large (∼2 MHz) and temperature independent, in contrast to the behaviour in conventional magnets. The thermal evolution of λ(T) for Er2Sn2O7 is somewhat similar to that of the Ti material. However, the depolarization curves remain exponential over the entire temperature range, suggesting a dense distribution of rapidly fluctuating magnetic moments, and, thus, are compatible with the absence of long-range order at least for T > 0.02 K.